PENENTUAN NILAI ASET PERUSAHAAN PENERBIT EFEK SYARIAH - Prasetyo, Totok Adhi (At-Tawazun, Jurnal Ekonomi Syariah, 2019)
The purpose of this study is to determine whether the capital structure, dividend policy, investment decisions and profitability as a determinant of the value of the issuer of Islamic securities companies. The value of the firm is proxyed by Price Book Value Ratio (PBV), the capital structure is proxied by Debt to Equity Ratio (DER), dividend policy is proxied by Dividend Payout Ratio (DPR), investment decision projected by Earning per Share (EPS), and Profitability proxied by Return on Assets (ROA) and Return on Equity (ROE). The population of this study are companies whose securities are listed in the List of Sharia Securities Year 2011-2013 as many as 365 companies. The sample of research is 56 companies with purposive sampling method. This type of research is descriptive quantitative. Data analysis used multiple linear regression analysis with SPSS 16 program. The result showed that DER, DPR, ROA did not have influence to firm value, ROE had significant positive effect to company, while EPS had significant negative effect to company value with significance level 0.000 ≤ 0.05.